To set up the distance formula between two points \( L(4,2) \) and \( M(7,6) \), we use the formula:
\[ d = \sqrt{(x_2 - x_1)^2 + (y_2 - y_1)^2} \]
Here, \( (x_1, y_1) = (4, 2) \) and \( (x_2, y_2) = (7, 6) \).
Substituting the values into the formula, we have:
\[ d = \sqrt{(7 - 4)^2 + (6 - 2)^2} \]
This simplifies to:
\[ d = \sqrt{(3)^2 + (4)^2} = \sqrt{9 + 16} = \sqrt{25} = 5 \]
Now, looking at the provided responses, the correct way to express this using the coordinates given is:
\[ d = \sqrt{(4 - 7)^2 + (2 - 6)^2} \]
Thus, the correct response is:
d=(4−7)²+(2−6)²−−−−−−−−−−−−−−−√
d is equal to square root of open paren 4 minus 7 close paren squared plus open paren 2 minus 6 close paren squared end root.